Distribution of fish fauna associated with a shipwreck in the southern Tyrrhenian Sea: vertical distribution and shipwreck structures. (December 2015) - Sinopoli, M.; Consoli, P.; Perzia, P.; Romeo, T.; Andaloro, F.
Summary: This study tested the hypothesis that the fish assemblage associated with a wreck can vary according to two factors: the vertical distribution and the level of wreck complexity. In the Southern Tyrrhenian Sea in September 2009, the composition and density of fishes were ascertained, coupling the detailed architectural reconstruction of a wreck with videos recorded by remotely operated underwater vehicles. A total of nine fish species were found. Anthias anthias followed by Clupeiformes dominated the upper zone of wreck, while in the lower zone a significant decrease in numbers of all fish species was recorded The study shows that vertical distribution is the factor most influencing the allocation of species, probably due to a greater exposure to the energy flows. In contrast, the complexity of the wreck appears to play a less important role, one that is in any case less clear. To clarify this point, further investigation with a higher resolution and a comparison with other wrecks should be performed.